2014
DOI: 10.1002/art.38410
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Renal Macrophages and Dendritic Cells From Lupus‐Prone Mice

Abstract: Objective To characterize renal macrophages and dendritic cells in two murine lupus nephritis models. Methods We used a bead based enrichment step followed by cell sorting to isolate populations of interest from young and nephritic mice. Cell morphology was examined by microscopy. Arginase and nitrite production were examined using biochemical assays. Antigen presentation function was determined using mixed lymphocyte reactions. Selected cytokine, chemokine and TLR profiles were examined using quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 55 publications
6
70
0
1
Order By: Relevance
“…These were originally described as a tissue-resident sentinel DC population; however, our data strongly support their reclassification as macrophages based on gene-expression profiling (31,54,55 (33).…”
Section: F4/80supporting
confidence: 65%
See 1 more Smart Citation
“…These were originally described as a tissue-resident sentinel DC population; however, our data strongly support their reclassification as macrophages based on gene-expression profiling (31,54,55 (33).…”
Section: F4/80supporting
confidence: 65%
“…It is unclear whether the CD11c + F4/80 + cells present in all strains are either macrophages or DCs. They were originally described as a kidney resident sentinel DC (31), but more recently they were reclassified as macrophages based on their morphological and functional features (32,33). Therefore, to confirm the ontogeny of these and our novel infiltrating CD11c…”
Section: Gene Expression Profiles Reveal Distinct Properties Of Disease-mentioning
confidence: 95%
“…In fact, no characteristic macrophage phenotype could be defined in lupus nephritis. Different reports showed that infiltrating macrophages/DCs in murine lupus nephritis are very heterogeneous (42,43). Nevertheless, mononuclear cells play a role in the pathogenesis of organ-related diseases, such as lupus nephritis, and are associated with chronic tissue damage and injury (44).…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of mononuclear cells plays a role in the progression of lupus nephritis and is associated with poor prognosis in SLE patients (45). Data from murine models of lupus nephritis suggest that macrophages and DCs infiltrating the kidneys represent a heterogeneous group and are derived from circulating peripheral monocytes (42,43). Sahu et al (42) found that the dominant macrophage subtype was not M1 or M2 and concluded that this phenotype might reflect an overall failure to resolve inflammation present in kidneys during flares.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation